2019
DOI: 10.14202/vetworld.2019.1273-1284
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with viral nervous necrosis in hybrid groupers in Malaysia and the high similarity of its causative agent nervous necrosis virus to reassortant red-spotted grouper nervous necrosis virus/striped jack nervous necrosis virus strains

Abstract: Background and Aim: Viral nervous necrosis (VNN) is a serious disease of several marine fish species. VNN causes 100% mortality in the larval stages, while lower losses have been reported in juvenile and adult fish. This study aimed to detect the occurrence of VNN while identifying its associated risk factors and the genotypes of its causative agent in a hybrid grouper hatchery in Malaysia. Materials and Methods: A batch of newly hatched hybrid grouper fry (Epinephelus fuscoguttatus X Epinephelus lanceolatus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Therefore, this study investigated the occurrence of NNV in subclinical, clinical, adult, and juvenile tilapia fish in the south of Egypt. Several clinical signs related to NNV were observed in examined fish, including skin darkening, abdominal swelling, high mortality rate (up to 70%), detached scales, hemorrhagic patches, exophthalmia and redness of organs, and exophthalmia and retina lesions; this is in agreement with Zorriehzahra et al ( 2014 ), Toffan et al ( 2016 ), Ariff et al ( 2019 ), and Taha et al ( 2020 ). RT-PCR results revealed that 66 out of 87 (75.9%) specimens were positive for NNV.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, this study investigated the occurrence of NNV in subclinical, clinical, adult, and juvenile tilapia fish in the south of Egypt. Several clinical signs related to NNV were observed in examined fish, including skin darkening, abdominal swelling, high mortality rate (up to 70%), detached scales, hemorrhagic patches, exophthalmia and redness of organs, and exophthalmia and retina lesions; this is in agreement with Zorriehzahra et al ( 2014 ), Toffan et al ( 2016 ), Ariff et al ( 2019 ), and Taha et al ( 2020 ). RT-PCR results revealed that 66 out of 87 (75.9%) specimens were positive for NNV.…”
Section: Discussionsupporting
confidence: 88%
“…NNV appeared to have a more significant effect on larger and adult fish than on smaller and younger (larval and juvenile) fish (Ariff et al 2019 ). Age is a primary risk factor for susceptibility to NNV (Hick et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the research results of Ariff et al [25] salinity does not affect the virus that causes VNN. There are no previous studies have reported that water pH, and high DO are supporting factors for VNN infection.…”
Section: Measurement Water Qualitymentioning
confidence: 93%
“…14,[16][17][18][19]21 Beyond its incidence in South Europe, RGNNV/SJNNV strains have been recently identified in gilthead seabream from Tunisia and Turkey rounding the Mediterranean coast, 22,23 as well as in farmed hybrid groupers (Epinephelus fuscoguttatus  Epinephelus lanceolatus) in Malasya (Figure 2). 15 The rapid spread of these reassortant strains underlines the urgent necessity of new preventive measures to control the spread of the virus. The presence of reassortant strains opened the door to designate asymptomatic carrier species such as gilthead seabream into highly susceptible, in which reassortant NNV currently generates high mortality rates.…”
Section: Nodavirusmentioning
confidence: 99%